2017 IEEE Manchester PowerTech 2017
DOI: 10.1109/ptc.2017.7981144
|View full text |Cite
|
Sign up to set email alerts
|

Distance relay performance in future converter dominated power systems

Abstract: Abstract-Increasing penetration of converter-based generations in power system has led to new system challenges. Short circuit power response from converter-based generations is different from that of traditional synchronous generators. Power electronic converters can be designed for over-current only up to 1.1-1.25 times of its nominal value. Low availability of short circuit power can cause many challenges such as misoperation of distance relays. The aim of this paper is to investigate the effect of converte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…The unbalanced voltages usually have undesirable impacts on power grid [2]. The unbalanced condition increases power losses in the grid and may deteriorate the operation of the protection relays [3], where the unbalanced voltage relay is applied to deal with such a problem. The unbalanced voltages also increase energy losses of the induction motors and decrease their efficiency and longevity [4].…”
Section: Introductionmentioning
confidence: 99%
“…The unbalanced voltages usually have undesirable impacts on power grid [2]. The unbalanced condition increases power losses in the grid and may deteriorate the operation of the protection relays [3], where the unbalanced voltage relay is applied to deal with such a problem. The unbalanced voltages also increase energy losses of the induction motors and decrease their efficiency and longevity [4].…”
Section: Introductionmentioning
confidence: 99%
“…Rijcke et al [12] discovered that the backup distance relay is not correctly performed during symmetrical faults because of the small fault current contribution of DFIG‐based wind turbines. Sarkar et al [13] studied the performances of zone‐2 distance relay in low short circuit power scenarios, and it indicates that improper reactive current control of wind turbines may result in maloperation. He et al [14] discovered the under‐reaches of the zone‐2 distance relay in offshore wind integration and voltage source converter–high‐voltage DC scenarios, and then proposed an impedance calculation method for preventing the maloperation.…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, the articles [5][6][7] and reports [2][3][4] reviewed the impacts and summarised the challenges from different perspectives. Secondly, a lot of research studies have focused on discovering the maloperation of the distance relay with numerical simulations and seeking possible solutions [8][9][10][11][12][13][14][15]. Hooshyar et al revealed some defects of distance protection relating to fault current contribution of different types of wind turbines and proposed a new pilot protection scheme [8][9][10].…”
Section: Introductionmentioning
confidence: 99%